Stakeholder workshop insights: Driving sustainability in the coffee value chain through traceability systems - Igeler, William; King, Brian; Wiegel, Jenny; Ceballos-Sierra, Federico; Colindres, Mirian; Reyes, Byron; Soto-Joya, Fernanda (CGIAR Initiative on Rethinking Food Markets, 2024)
On March 19, 2024, at the Clarion Hotel in Tegucigalpa, Honduras, the Alliance of Bioversity International & CIAT convened a workshop focused on the interoperability of traceability systems and their importance in complying with the European Union Regulation on Deforestation-Fee Products (EUDR). This workshop, which was arranged by the Alliance team and titled “Common Interests and Joint Solutions for EUDR Compliance: A Roadmap Towards Interoperability of Traceability Systems”, gathered 33 stakeholders from various institutions involved in the coffee sector and agricultural supply chain in Honduras.